Mechanism study about the adsorption of Pb(II) and Cd(II) with iron-trimesic metal-organic frameworks - Zhang, Bao-Lin; Qiu, Wei; Wang, Pan-Pan; Liu, Yu-Lei; Zou, Jing; Wang, Lu; Ma, Jun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Adsorption of Pb and Cd nearly approached equilibrium in the initial 2 min.•More negative hydration enthalpy (ΔHhydΘ) and larger ionic radius of Cd led to its inferior removal performance.•BDM electrical double layer model can illustrate adsorption mechanism.•Fixed-bed adsorption experiments showed effective filtration volume of 980 mL for Pb and 300 mL for Cd. This study examined the effects of two kinds of iron-trimesic metal-organic frameworks (MOFs) [MIL-100(Fe) and Fe-BTC] on adsorption of Pb(II) and Cd(II). For both materials, adsorption of Pb and Cd nearly approached equilibriums in the initial 2 min with high pseudo-second-order kinetics rate constants (0.895 g·mg−1·min−1 for Pb and 1.416 g·mg−1·min−1 for Cd). Both materials showed better adsorption performance with the increase of solution pH (from 2 to 7). Adsorption processes were endothermic, entropy-increased and spontaneous. The higher enthalpy change (ΔH0) and entropy change (ΔS0) values for Cd adsorption reflected the more difficult adsorption of Cd compared with Pb, which is related with more negative hydration enthalpy (ΔHhydΘ) and larger ionic radius of Cd. Multilayer adsorption phenomena appeared with no maximum adsorptive capacity observed. Both Langmuir-Freundlich and Freundlich-BET models could well describe isotherms. Multilayer adsorption may be attributed to the formation of inner-sphere complexation and outer-sphere complexation. Bockris-Devanathan-Muller (BDM) electrical double layer theory was used for illustrating adsorption mechanism. The fixed-bed adsorption experiments with Fe-BTC showed outstanding elimination performance in initial operating period (>99.8% for Pb and >99.6% for Cd), with effective filtration volume of 980 mL for Pb and 300 mL for Cd. Recyclability test showed that Fe-BTC could be well regenerated by ethylenediamine tetraacetic acid disodium salt (EDTA-2Na). This study showed that MIL-100(Fe) and Fe-BTC are potential for practical heavy metal removal applications.